2022
DOI: 10.1021/acs.nanolett.2c00711
|View full text |Cite
|
Sign up to set email alerts
|

Synergetic Charge Transfer and Spin Selection in CO Oxidation at Neighboring Magnetic Single-Atom Catalyst Sites

Abstract: Deciphering the precise physical mechanism of interaction between an adsorbed species and a reactive site in heterogeneous catalysis is crucial for predictive design of highly efficient catalysts. Here, using first-principles calculations we identify that the two-dimensional ferromagnetic metal organic framework of Mn 2 C 18 H 12 can serve as a highly efficient single-atom catalyst for spin-triplet O 2 activation and CO oxidation. The underlying mechanism is via "concerted charge-spin catalysis", involving a d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 67 publications
1
34
0
Order By: Relevance
“…Note that the optimized Mn 1 @g-C 3 N 4 /CeO 2 (111) complex possesses 15 μB MM. Upon the spin-triplet O 2 adsorption, the total MM of the O 2 /Mn 1 @g-C 3 N 4 /CeO 2 (111) system is 17 μB, obeying the spin conservation. The relative energies with different spin configurations of Mn 1 @g-C 3 N 4 /CeO 2 (111) and O 2 /Mn 1 @g-C 3 N 4 /CeO 2 (111) systems are presented in Figure S5. Specifically, as shown in Figure b, we also analyze the spin transfer Δ M in the O 2 adsorption process.…”
mentioning
confidence: 93%
See 2 more Smart Citations
“…Note that the optimized Mn 1 @g-C 3 N 4 /CeO 2 (111) complex possesses 15 μB MM. Upon the spin-triplet O 2 adsorption, the total MM of the O 2 /Mn 1 @g-C 3 N 4 /CeO 2 (111) system is 17 μB, obeying the spin conservation. The relative energies with different spin configurations of Mn 1 @g-C 3 N 4 /CeO 2 (111) and O 2 /Mn 1 @g-C 3 N 4 /CeO 2 (111) systems are presented in Figure S5. Specifically, as shown in Figure b, we also analyze the spin transfer Δ M in the O 2 adsorption process.…”
mentioning
confidence: 93%
“…For many important oxidization processes particularly those that involve O 2 , the activation of O 2 involves a spin-multiplicity transition from the triplet to singlet, which is generally a fundamental key step accomplished by filling the antibonding orbitals with a pair of minority spins in the framework of a spin-selection rule. Therefore, the development of highly efficient magnetic single-atom catalysts (MSAC) with magnetic active centers facilitating the activation of spin-triplet O 2 via appropriate spin–spin coupling channels is crucial to reveal the microscopic reaction mechanism of the interaction between the adsorbed species and the reactive site in heterogeneous catalysis. Along this line, recent studies revealed that the spin state of the catalytic active sites may play an important role in regulating the catalytic performance for some chemical processes.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The demonstrated ability to synthesize and control a series of complex clusters with variable stoichiometries and to probe their reactivitiesin particular water oxidation and O–O couplingunder reaction conditions that allow detailed comparisons with systematic first-principles simulations of the reaction pathways provides the impetus for further experimental and theoretical explorations using the hierarchical synthetic modeling strategy developed in this series of investigations. The uncovering of the subtle interplay between reactive pathways evolving on neighboring spin-isomeric potential-energy landscapes, belonging to ferromagnetically ordered majority spin manifolds, and of spin-gated selective processes steered by spin-conserving selection rules is expected to guide future probing of the OEC, as well as further development of catalysts for oxygen evolution reactions with an added emphasis on the role of spin, doping by magnetic atoms, magnetic ordering, synergetic spin and charge-transfer processes, and magnetic-field effects on such reactions. ,, …”
Section: Discussionmentioning
confidence: 99%
“…The importance of spin selectivity is currently gaining growing research interest, particularly in the context of explorations targeting electrochemical water oxidation reactions, as well as in studies of spin selection in catalyzed CO oxidation . Based on such studies, a ligated CaMn 4 O 5 cofactor cluster model of the S 4 state has been recently employed in theoretical modeling, which shows that O–O formation is possible with accessible energy barriers when the cluster is in an optimal ferromagnetic state, which is conserved , throughout the reaction, thus suggesting an alternative to the mechanism based on a ferrimagnetic S3 state offered in ref .…”
Section: Introductionmentioning
confidence: 99%